Pelatihan Pembuatan Modul Digital Untuk Meningkatkan Kompetensi Guru Sekolah Dasar Di Kabupaten Sumedang - Saputra, Yudha Munajat; Enjang Yusup Ali; Susilawati, Dalia (Jurnal SOLMA, 2024)
Digital module development training in elementary schools is an activity that aims to improve the competence of teachers in elementary schools, especially in the skills of utilizing technology. Lecturers as agents of change as well as facilitators in the training work together with principals and teachers in developing better teacher competencies. The training was attended by 11 elementary school teachers in Sumedang Regency. In the preparation stage, a needs analysis was conducted to determine the problems that arise related to learning that integrates technology. Based on these problems, an action plan was developed to overcome the problems that occurred. Furthermore, at the training implementation stage, materials related to the creation of digital modules and hands-on practice were given to improve the ability to develop digital modules. After the training, an evaluation was carried out by holding a reflection of the measurement training participants after the implementation of the module making training. This training has contributed to improving teacher competence through the use of technology and creativity by making interactive learning materials.